Perancangan Komunikasi Visual Keyna Galeri Ploso Jombang Berbasis Media Promosi Guna Meningkatkan Brand Awareness - Firdaus, Gitra Dana; Karsam, Karsam; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2016)
The aim of this thesis was to design a Visual communication Keyna Gallery Ploso Jombang Based Media promotion to enhance Brand awareness. This event will be based by the lax visitors that come to Keyna Gallery Ploso Jombang of students, college students, and the community. Whereas one of the main goals of the Foundation of Keyna Gallery Ploso Jombang is able to provide containers for students, students and communities wishing to increase the power of creativity and the appreciation of art. The data obtained have an important role to know the outline of the problems encountered in the design of visual communication Keyna Gallery Ploso Jombang Based Media promotion to enhance Brand Awareness. The data collection using qualitative research include observation, focus group discussion, interview and case study. So that the collected data is more complete, also supported data collection techniques among others, librarianship and documentation. Technique of data analysis in this study uses qualitative methods of analysis-descriptive. The descriptive interpretation of data is done with the reasoning that is based on data that has been collected After the required data has been collected, carried out the processing or analysis of data that include data reduction, categorization, and put together a working hypotheses or conclusion data analysis is carried out by several stages, namely the reduction, the presentation of data, and conclusions. A data reduction technique is a simplification of answers all the questions that have been submitted to the parties in a particular data collection techniques, later focused on matters relating to the media promotion Keyna Gallery Ploso Jombang. The design of promotional media will use the concept of "Impressive". Description of the "Impressive '' means it can leave an impression that in the aim to inform the public about the existence of Keyna Gallery Ploso Stubs could be a container and art appreciation for the unreleased artists from SD-student and to be able to leave an impression for the visit and has talent that facilitates Gallery Keyna to hold the exhibition so that their work can be appreciation and known by many audiences. As specified in the keyword the result of the merger of keyword data interview, study literature, swot analysis, usp, and stp which has gone through a number of search process so that it is making a concept of "Impressive" as the basis for the main staple in the design of Visual communication-based Gallery Keyna Media promotion to enhance Brand Awareness. Keywords: Keyna Gallery Ploso Jombang, Media Promotion, Brand Awareness